Improving Child Safety Through Health Education Underwear Rules, Growth Monitoring, And Disaster Preparedness - Sofia Februanti; Ai Cahyati; Dini Mariani; Novi Enis Rosuliana (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Schools are part of a community unit consisting of students, teachers, principals, and other employees. Elementary students and teachers, as well as employees, will spend a lot of time at the school. Many problems can be helped to solve in schools, such as preventing sexual violence through underwear rules, monitoring growth and development, and disaster preparedness. All of these activities can be carried out in a series of community service activities at an elementary school (SD) in the city of Tasikmalaya. Community service activities are applications of research results conducted by lecturers at the Nursing Study Program, Department of Nursing, Poltekkes, Ministry of Health, Tasikmalaya. The method of activities carried out included the provision of health education about underwear rules, measuring the weight and height of elementary school children, and how to manage disaster mitigation in the Tasikmalaya area. The facilities and infrastructure used are laptops, in focus, body scales, height measurements, and disaster simulation tools. The results of the activity include an increase in the knowledge and skills of participants or elementary school children about underwear rules and disaster mitigation. Most elementary school children have growth that is by their age